Low impact development modeling to manage urban stormwater runoff: case study of Gorzów Wielkopolski - Nowogoński, Ireneusz (Journal of Environmental Engineering and Landscape Management, 2020)
Uncontrolled urbanization causes local flooding and deterioration of the water quality of receivers as a result of an increase in peak flow rate and increased washing out of contaminants from the catchment area. Currently, classic storage tanks are most often used. An alternative solution may be the use of Low Impact Development (LID), i.e. the preservation and restoration of natural landscape elements, minimizing the imperviousness of the catchment in the form of rain barrels, permeable walkways or bio-retention reservoirs. The comparison of both techniques was carried out using the Environmental Protection Agency Storm Water Management Model (EPA SWMM). The influence of several solutions on a selected urbanized catchment located in Gorzów Wielkopolski was tested.